The viral protein VP6 of rotavirus coinmunoprecipated with HSC70 in cels MA104 - Luz Stella Rodríguez; Carlos Arturo Guerrero Fonseca (Revista de la Facultad de Medicina, 2006)
Introduction: Rotaviruses are the main cause of gastroenteritis in children under five years old. At this moment is unknown how these viruses entry to host cell. The heat shock cognate protein HSC70 has been involved in rotavirus cell entry. However, the relationship between rotavirus proteins and HSC70 has not been established.